Microneedling combined with compound betamethasone in treatment of severe alopecia areata: A case report - Pei, Danning; Chen, Lirong; Yao, Yue; Zeng, Linxi; Zhang, Guoqiang (Frontiers in Immunology, 2022)
Alopecia areata (AA) is a common inflammatory, non-cicatricial hair loss. At present, it is considered that its pathogenesis is an autoimmune disease specific to hair follicle organs mediated by T cells under the combined action of genetic and environmental factors. Treatment is challenging for children with severe AA who are resistant or intolerant to conventional treatment.Here, we treated a 3-year-old child with severe AA with microneedling combined with compound betamethasone. After 6 months of treatment, the patient's condition was significantly improved, and most of the primary hair loss areas had hair regeneration.